Analysis Certification Teachers On Teacher Professional Education In Service - Sri Uchtiawati (INNOVATION RESEARCH JOURNAL, 2020)
The problem of this research is the need to improve the quality of Education, which in the analysis obtained by a base to enhance the quality of Education. Knowledge lies in the sub-system of teachers because basically, the teacher is learning agent. And how the efforts to upgrade the quality of Education is then, by invitation Act s item of national Education and law teacher and lecturer, is it relieved l formal that teachers must have a teaching certificate, or known as a teacher's certificate (sergu). The essence of teacher certification award "teaching certificate" on teachers, which meets the standards of professional, considering teacher professionals is a prerequisite for creating quality education. The purpose of this study is shortly analysis implementation of teacher certification through Professional Teacher Education In Position (PPGJ). The research method was done by qualitative descriptive, where researcher as a key instrument, which begins from preliminary studies, followed by collecting the data by using a technique sheets observation, interviews and documentation, then triangulation, and the reduction of the data. This research was conducted at PT Muhammadiyah, which held PPG Daljab in 2018 for two periods, and in 2019 for three periods. Results from this study that professional teachers can be evidenced by the Certified Master (Gr) can be obtained one through I Professional Teacher Education in the office, with the provision begins academic selection and administration, and only after the deepening of the material model of hybrid learning on Spada and ID REN the amount of 10 credits, diving three months. Workshops and Pearteaching execution of this study in Unmuh Gresik as LPTK amount of load are 8 credits for five weeks, continue VING PPL in school partners LPTK number 6 credits for three weeks, to end activities do SMEs of PPG consisting is test-related the implementation of learning carried out in partner schools and UP is a centralized online knowledge test, a maximum graduation grace period of 2 years with six times the UP retest. Furthermore, for teachers who have passed the PPG Daljab can meng ask Teacher Certification (sergur) to receive allowances, and got the facilities that support achievement for teachers, including structural positions provided by the school. The d nature of learning and mastery learning do teachers better, so Influence of Community belief against schools with teachers who already have a teacher's certificate (Gr) is large enough, can make one-factor improvement of the accreditation status of the school. Thus, schools should be able to provide support to teachers to have the opportunity to take part in the PPG in Position Program